(untitled) (Research, Society and Development, 2020)
Jelly is a product very appreciated by Brazilians, being considered an alternative for the use of fruits. The objective, through this research and elaboration of mandacaru and yellow passion fruit jelly, is to evaluate as microbiological conditions. The experiment was conducted at the Microbiology Laboratory of the Federal University of Campina Grande. To make extra gelatin has been used fruits: 50:50 sugar, adding 40% water. For this, the fruits were beaten in a blender with water, sieved and the juice was added to the sugar, being taken to low heat (180 ± 1 ° C). The verification of the jelly point was based on the content of soluble solids (62%). The determination of microbiological parameters followed the methodology recommended by the American Public Healh Association and the parameters of quality control. A mandacaru and yellow passion fruit jelly is a product derived from the processing of passion fruit pulp and whole mandacaru. For quality microbiological analyzes verified, if there is no Salmonella sp., Total coliforms and thermotolerant count <3 NMP / g and values <1 x 104 CFU / g for bacterial count and aerobic statistics, being within the tolerance limit established by RDC Legislation No. 12, of January 2, 2001. Conclude if the preparation method is easy to perform and low cost, being a potential alternative for the valorization of local and regional ingredients. The jelly was treated under ideal hygiene conditions, showing good microbiological quality to be used safely.